Effects of bisphenol-A (BPA) on body weight, hematological parameters and histo-texture of kidney in swiss albino mice (Asian Journal of Medical and Biological Research, 2021)
Bisphenol-A (BPA) is one of the highest volume chemicals produced world-wide and used in the manufacture of plastics and epoxy resins that are pervasive in our environment and daily lives. The present research was carried out to investigate the effects of two different doses of Bisphenol-A (BPA) on the body weight, hematological parameters and patho-physiological changes of kidney in mice. For this study, fifteen mice, 6 to 8 weeks of age with an average bwt 27.10±0.5 gm, were randomly divided into three groups (n= 5). Group A (control) received only normal mouse pellet while group B and group C received pellet mixed with BPA @ 50 mg and 100 mg / kg bwt daily for 12 weeks, respectively. At the end of the experiment, blood and tissues were collected and processed for hematological and histopathological examination. Results showed that BPA- treated mice caused significant elevation (p